Bedaquiline-containing regimens in patients with pulmonary multidrug-resistant tuberculosis in China: focus on the safety - Jing-Tao Gao; Juan Du; Gui-Hui Wu; Yi Pei; Meng-Qiu Gao; Leonardo Martinez; Lin Fan; Wei Chen; Li Xie; Yu Chen; Hua Wang; Long Jin; et al. (BMC, 2021)
Abstract Background World Health Organization recommends countries introducing new drug and short treatment regimen for drug resistant tuberculosis (DR-TB) should develop and implement a system for active pharmacovigilance that allows for detection, reporting and management of adverse events. The aim of the study is to evaluate the frequency and severity of adverse events (AEs) of bedaquiline-containing regimen in a cohort of Chinese patients with multidrug-resistant (MDR)/extensively drug-resistant (XDR)-TB based on active drug safety monitoring (aDSM) system of New Drug Introduction and Protection Program (NDIP). Methods AEs were prospectively collected with demographic, bacteriological, radiological and clinical data from 54 sites throughout China at patient enrollment and during treatment between February, 2018 and December, 2019. This is an interim analysis including patients who are still on treatment and those that have completed treatment. A descriptive analysis was performed on the patients evaluated in the cohort. Results By December 31, 2019, a total of 1162 patients received bedaquiline-containing anti-TB treatment. Overall, 1563 AEs were reported, 66.9% were classified as minor (Grade 1-2) and 33.1% as serious (Grade 3-5). The median duration of bedaquiline treatment was 167.0 [interquartile range (IQR): 75-169] days. 86 (7.4%) patients received 36-week prolonged treatment with bedaquiline. The incidence of AEs and serious AEs was 47.1% and 7.8%, respectively. The most frequently reported AEs were QT prolongation (24.7%) and hepatotoxicity (16.4%). There were 14 (1.2%) AEs leading to death. Out of patients with available corrected QT interval by Fridericia's formula (QTcF) data, 3.1% (32/1044) experienced a post-baseline QTcF ≥ 500 ms, and 15.7% (132/839) had at least one change of QTcF ≥ 60 ms from baseline. 49 (4.2%) patients had QT prolonged AEs leading to bedaquiline withdrawal. One hundred and ninety patients reported 361 AEs with hepatotoxicity ranking the second with high occurrence. Thirty-four patients reported 43 AEs of hepatic injury referred to bedaquiline, much lower than that referred to protionamide, pyrazinamide and para-aminosalicylic acid individually. Conclusions Bedaquiline was generally well-tolerated with few safety concerns in this clinical patient population without any new safety signal identified. The mortality rate was generally low. These data inform significant positive effect to support the WHO recent recommendations for the wide use of bedaquiline.